The Influence of Customer Experience, Service Quality, and Customer Satisfaction on Parental Choice of Splus Education - Lia Fransisca; Danial Thaib (Politeknik Siber Cerdika Internasional, 2025)
This study aims to examine the influence of customer experience and service quality on parents' decisions in choosing tutoring institutions, mediated by customer satisfaction at Splus Education in West Jakarta. The research method used is quantitative, with a causal study approach to test the causal relationship between variables. The variables used are customer experience and service quality as independent variables, customer satisfaction as the mediating variable, and parents' decisions as the dependent variable. The measurement scale employed is an interval scale using the Likert scale method. The population consists of parents who registered their children at Splus Education in West Jakarta, with a sample size of 90 respondents. The data analysis technique uses PLS-SEM with the Smart PLS 4.4.4 tool. The results indicate that customer experience has a positive effect on parents' decisions mediated by customer satisfaction. Meanwhile, service quality has a positive and significant effect on parents' decisions mediated by customer satisfaction. Customer experience significantly influences customer satisfaction, service quality significantly influences customer satisfaction, and customer satisfaction significantly influences parents' decisions. However, customer experience does not significantly influence parents' decisions directly.